Hospital acquired urinary tract infection by multidrug-resistant Brevundimonas vesicularis - Puneet K Gupta; Suma B Appannanavar; Harsimran Kaur; Vikas Gupta; Balvinder Mohan; Neelam Taneja (Wolters Kluwer Medknow Publications, 2014)
Infections caused by Brevundimonas vesicularis, a nonfermenting Gram-negative bacterium, are very rare. Here, we report the first case of multidrug-resistant hospital acquired urinary tract infection by B. vesicularis. Patient was successfully treated with antimicrobial therapy with piperacillin-tazobactam and amikacin.